Economia & gestão (Programa de Pós-Graduação em Administração, PPGA da PUCMinas, 2001)
"Mission: Disseminate the scientfic production in the following areas: Management strategy, marketing, human resources management, innovation management, information and knowledge management, research and teaching in management, organizational studies and public adminsitration."